Evaluation of Economic Impact of Universities on Regional Development - Vasyliv Volodymyr B.; Beztelesna Lyudmyla I (Bìznes Inform, 2019)
The impact of a university on regional subsystems: political, demographic, economic, infrastructural, cultural one is highlighted. It is established that the existing foreign models evaluate the direct, indirect and induced impact of universities on regional economic development. The most popular methodology for studying economic impact of universities on the regional economy is the ACE methodology. It is proved that its use in Ukraine meets certain difficulties due to the lack of statistical data. Statistical data in Ukraine do not allow for evaluating the indirect economic impact of university expenditures and calculating the corresponding multiplicative effect. Domestic approaches to evaluating the impact of universities on economic development are analyzed. The impact of universities in the UK and Ukraine on regional economic development is compared. Using the example of National University of Water and Environmental Engineering, the impact of the university on the economy of the Rivne region is analyzed. The ways for adapting world experience to domestic realities are proposed.